The Validity Of Contracts And Ethics Of Tiktok Affiliate Marketing From The Perspective Of Fiqh Muamalah - Mohammad Samsul Arifin; Muhammad Juhariyanto; Alfiyanto (Pascasarjana, Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2026)
The TikTok Affiliate Program, integrated within the TikTok Shop ecosystem, has become a significant digital business phenomenon in Indonesia, particularly among the Muslim community. This study aims to examine the validity of contracts (akad) within the TikTok affiliate program based on the principles of fiqh muamalah, and to evaluate digital business ethics according to maqasid al-shariah and the characteristics of Islamic marketing. Using a normative qualitative approach, this research analyzes classical fiqh literature, electronic commerce regulations, and TikTok affiliate practices. The findings indicate that the TikTok affiliate program can be classified as an agreement of ju‘alah or samsarah, which is considered valid under Islamic law as long as it fulfills the conditions of lawful objects, contract transparency, and the absence of gharar (uncertainty) or riba (usury). However, ethical challenges such as misleading promotions and regulatory violations—necessitate the strengthening of sharia-based guidelines. This study recommends fiqh muamalah education for affiliates and the development of sharia-based regulations by the TikTok platform to ensure ethical digital business practices.